2012
DOI: 10.1007/s00404-012-2652-4
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual versus vaginal misoprostol for cervical ripening before hysteroscopy: a randomized clinical trial

Abstract: Sublingual route of misoprostol could be considered as an effective medication before surgical hysteroscopy in perimenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…We tried in this study to find if there were any positive or negative consequences of using different dosages of oral misoprostol. Hence, 200 and 400 µg sublingual misoprostol had been shown to be effective for cervical priming in pregnant women [13] and before surgical hysteroscopy in peri-menopausal women [14]. Four hundred micrograms of oral or vaginal misoprostol is found useful for cervical dilatation up to 10 mm prior to operative hysteroscopy [15].…”
Section: Discussionmentioning
confidence: 99%
“…We tried in this study to find if there were any positive or negative consequences of using different dosages of oral misoprostol. Hence, 200 and 400 µg sublingual misoprostol had been shown to be effective for cervical priming in pregnant women [13] and before surgical hysteroscopy in peri-menopausal women [14]. Four hundred micrograms of oral or vaginal misoprostol is found useful for cervical dilatation up to 10 mm prior to operative hysteroscopy [15].…”
Section: Discussionmentioning
confidence: 99%
“…24 In addition, there exists high-quality evidence that cervical ripening with sublingual administration of 400 mg misoprostol is more effective in postmenopausal women compared with alternative routes of administration. 25,26 There are emerging data regarding the use of vaginal prostaglandin E 2 (dinoprostone) in reproductive aged women before hysteroscopic procedures. In a double blinded randomized controlled trial of a total 49 patients, 10 mg of vaginal dinoprostone was reported to be a more effective cervical priming agent than both placebo and 400 mg vaginal misoprostol.…”
Section: Risk Reduction Recognition and Management Of Access-relatementioning
confidence: 99%
“…Misoprostol (prostaglandin E1 analog) is used widely for cervical ripening, labor induction, postpartum hemorrhage and second trimester terminations [11,12]. It could increase myometrial contraction and decrease hemorrhage [10].…”
Section: Introductionmentioning
confidence: 99%